Targeting exon 20 insertion mutations in lung cancer. Issue 1 (15th January 2023) - Yang, Yaning; Wang, Yan
Abstract : Purpose of review: The application of tyrosine kinase inhibitor (TKI) has successfully changed the standard of care in epidermal growth factor receptor ( EGFR ) positive non-small cell lung cancer. However, clinical survivals for patients with EGFR exon 20 insertions have failed to improve over the long period and the mutation appeared resistant to EGFR -TKIs. This overview focused on the current treatment strategies, summarized the emerging regimens for patients with EGFR exon 20 insertions, and demonstrated historical challenges and future development. Recent finding: Current clinical trials suggested that several regimens selectively-targeted EGFR exon 20 insertions presented potent antitumor activity, like mobocertinib and the bispecific anti- EGFR-MET monoclonal antibody amivantamab and were approved by Food and Drug Administration (FDA) in patients progressed beyond first-line treatment. Novel treatments, including DZD9008, CLN-081, revealed modest clinical efficacy as well and clinical trials are underway, which may lead to improvement of survival outcomes. Summary: Recent clinical evidence indicates that targeted therapies could improve survival benefits to some extent. More efforts on drug development are underway to bring higher response rates both extracranial and intracranial, sustained clinical remission, and better survival benefits.